2013
DOI: 10.1007/s10096-013-2037-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China

Abstract: In order to assess the prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China, we conducted a polymerase chain reaction (PCR)-based surveillance of OXA-type β-lactamase gene clusters for a total of 2,880 Acinetobacter spp. isolates collected from 23 Chinese provinces. All isolates were tested for susceptibility to 12 antimicrobial agents and showed high rates of resistance to all these agents except minocycline. We also found that the vast majority of carbapenem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
3
24
2
Order By: Relevance
“…Mohajeri et al (2013) reported that blaOXA-51-like and blaOXA-23-like genes were the predominant mechanisms of resistance to imipenem in A. baumannii. However, certain results of previous studies appear to be inconsistent with those of our study (Jeannot et al, 2014;Ji et al, 2014;Xia et al, 2014;Mohajeri et al, 2015). One study reported that only blaOXA-23 and blaOXA-51 were amplified in 96.7% of the A. baumannii strains, while neither blaOXA-24 nor blaOXA-58 was amplified (Xia et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Mohajeri et al (2013) reported that blaOXA-51-like and blaOXA-23-like genes were the predominant mechanisms of resistance to imipenem in A. baumannii. However, certain results of previous studies appear to be inconsistent with those of our study (Jeannot et al, 2014;Ji et al, 2014;Xia et al, 2014;Mohajeri et al, 2015). One study reported that only blaOXA-23 and blaOXA-51 were amplified in 96.7% of the A. baumannii strains, while neither blaOXA-24 nor blaOXA-58 was amplified (Xia et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Jeannot et al (2014) reported that blaOXA-23 and blaOXA-24 were the most frequently detected genes in isolated A. baumannii. Ji et al (2014) reported that blaOXA-24 and blaOXA-58 have emerged as potential threats for hospital outbreaks of multidrug-resistant A. baumannii. Mohajeri et al (2015) observed that blaOXA-23-like gene were the main genes of A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter isolates have shown a complex interaction of multiple mechanisms of resistance to carbapenems, with the production of naturally occurring oxacillinases (OXA) and the absence of PBP2 being most commonly observed; for some isolates, an additional downregulation of porin expression and subsequent reduction in carbapenem entry has been observed (138). The predominant oxacillinases (OXA-23, OXA-24 or -40, OXA-51, OXA-58, and OXA-143) are responsible for the majority of phenotypic resistance to carbapenems detected in the United States, Latin America, Europe, Asia, and in many parts of the world (31,(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150). OXA-23 is a plasmid-or transposonencoded ␤-lactamase, while OXA-51 is a chromosome-based enzyme and is intrinsic to Acinetobacter.…”
Section: Antibiotic Resistance Drives Outcomesmentioning
confidence: 99%
“…Some superbugs accurately catalyze the hydrolysis of the β-lactam ring in β-lactam antibiotics through their target enzyme, TEM-1 β-lactamases, and thereby lead to the antibiotics losing efficacy against them (1). The recognition and binding of TEM-1 β-lactamase with the antibiotics is a precondition for the hydrolysis of the antibiotics (2).…”
Section: Introductionmentioning
confidence: 99%